Enhancing Infection Prevention and Control Capacity in Health Facilities Following the 2019 Ebola Outbreak in Kasese, Uganda. (October 2020) - Kesande, Maureen; Lamorde, Mohammed; Bancroft, Elizabeth; Herzig, Carolyn; Nanyondo, Judith; Omuut, Winifred; Walwema, Richard; Nelson, Lisa; Brown, Vance; Mutoro, Julius; Wilkinson, Colby; Nakiire, Lydia; et al.
Abstract : Background: In June 2019, 3 people were diagnosed with Ebola virus disease (EVD) in Kasese district, Uganda, all of whom had come from the Democratic Republic of Congo (DRC). Although no secondary transmission of Ebola occurred, an assessment of infection prevention and control (IPC) using the WHO basic IPC facility assessment checklist revealed significant gaps. Robust IPC systems are critical for the prevention of healthcare-associated infections like EVD. A rapid intervention was developed and implemented in Kasese to strengthen IPC capacity in high-risk facilities. Methods: Of 117 healthcare facilities, 50 were considered at high risk of receiving suspected EVD cases from DRC based on population movement assessments. In August 2019, IPC mentors were selected from 25 high-risk facilities and assigned to support their facility and a second high-risk facility. Mentors ensured formation of IPC committees and implemented the national mentorship strategy for IPC preparedness in non-EVD treatment facilities. This effort focused on screening, isolation, and notification of suspect cases: 4 mentorship visits were conducted (1 per week for 1 month). Middle and terminal assessments were conducted using the WHO IPC checklist 2 and 4 weeks after the intervention commenced. Results were evaluated against baseline data. Results: Overall, 39 facilities had data from baseline, middle, and end assessments. Median scores in facility IPC standard precautions increased from baseline 50% (IQR, 39%–62%) to 73% (IQR, 67%–76%) at the terminal assessments. Scores increased for all measured parameters except for water source (access to running water). Greatest improvements were seen in formation of IPC committees (41% to 75%), hand hygiene compliance (47% to 86%), waste management (51% to 83%), and availability of dedicated isolation areas (16% to 42%) for suspect cases. Limited improvement was noted for training on management of suspect isolated cases and availability of personal protective equipment (PPE) (Fig. 1). No differences were noted in scores for facilities with nonresident mentors versus those with resident mentors at baseline (48% vs 50%) and end assessments (72% vs 74%). Conclusions: This intervention improved IPC capacity in health facilities while avoiding the cost and service disruption associated with large-scale classroom-based training of health workers. The greatest improvements were seen in activities relying on behavior change, such as hand hygiene, IPC committee, and waste management. Smaller changes were seen in areas requiring significant investments such as isolation areas, steady water source, and availability of personal protective equipment (PPE). Mentorship is ongoing in moderate- and lower-risk facilities in Kasese district. Funding: None Disclosures: Mohammed Lamorde reports contract research for Janssen Pharmaceutica, ViiV, Mylan.